2018
DOI: 10.1186/s13071-018-2956-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of fluralaner and commonly used acaricides against Dermanyssus gallinae isolates from Europe and Brazil

Abstract: BackgroundThe poultry red mite Dermanyssus gallinae negatively impacts bird welfare and health, and interferes with egg production and quality, while emerging acaricide resistance limits control options. Fluralaner, a novel miticide for administration in drinking water, is approved for control of D. gallinae infestations. Mite sensitivity testing is relevant to gauge field isolate susceptibility to available treatments.MethodsThirteen D. gallinae isolates collected during 2014 through 2016 from farms in German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Pyrethroids, such as λ-cyhalothrin and bifenthrin, were largely used in poultry farms to fight the house fly Musca domestica L. (Abbas et al, 2016), and this may have contributed to selection of resistant individuals of D. gallinae, too. This could account for the early rise of resistant D. gallinae populations, which was firstly documented more than 20 years ago (Beugnet et al, 1997) and it has been repeatedly reported from mites collected in poultry farms (Nordenfors et al, 2001;Thomas et al, 2018). A similar trend was observed for O. sylviarum populations collected in the field in California (Mullens et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Pyrethroids, such as λ-cyhalothrin and bifenthrin, were largely used in poultry farms to fight the house fly Musca domestica L. (Abbas et al, 2016), and this may have contributed to selection of resistant individuals of D. gallinae, too. This could account for the early rise of resistant D. gallinae populations, which was firstly documented more than 20 years ago (Beugnet et al, 1997) and it has been repeatedly reported from mites collected in poultry farms (Nordenfors et al, 2001;Thomas et al, 2018). A similar trend was observed for O. sylviarum populations collected in the field in California (Mullens et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
“…Conversely, out of the three tested drugs, phoxim was the only one authorized for use in the presence of animals in poultry farms of Italy, and its operating procedures were adequately conceived and set up, especially in terms of dosage and administration schedule. This fact may have helped to keep low the proportion of resistant groups of D. gallinae, insomuch that less susceptible populations have recently been detected (Thomas et al, 2018). In this investigation, phoxim-resistant populations were only found in 2015, and it is possible that factors other than contacts with acaricides should be intervened.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Anecdotal evidence suggests that these products have a high efficacy rate at the doses labelled for flea and tick prevention against parasites including Demodex species, Sarcoptes species, Otodectes species, Cheyletiella species, Lynxacarus species and various poultry mites 2 12–15. Use in off‐label hosts including poultry, pigs, rabbits, hedgehogs and wildlife suggest this drug class has a wide margin of safety 16–24. Consideration for use in human beings using porcine models of disease may lead to promising breakthroughs in control of parasitic infections in endemic regions of the world 25.…”
Section: Discussionmentioning
confidence: 99%
“…Positive results are followed by field testing, which by necessity involves large numbers of parasites and hens in order to account for the many variables involved in infestation of hens within a henhouse (e.g. Bartley et al , 2015 ; Bartley et al , 2017 ; Thomas et al , 2018 ; Wright et al , 2016 ). The in vitro method of testing novel systemic control compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%